Sand Dams as a Potential Solution to Rural Water Security in Drylands: Existing Research and Future Opportunities - Ritchie, Hannah; Eisma, Jessica A.; Parker, Alison (Frontiers in Water, 2021)
Sand dams, a rainwater harvesting technique, are small dams constructed across ephemeral streams. During the rainy season, water is stored in the sand that accumulates behind the dam. Sand dams provide communities in drylands with water during the dry season via scoop holes, pools, and shallow wells. Whilst many studies portray sand dams as a positive solution to the growing threat of dryland water insecurity, others highlight their challenges, including poor water quality, evaporation and leakage from some dams, and the contested failure rate and ability of dams to provide water year-round. This article reviews the peer-reviewed and grey literature on sand dams discovered through Scopus and Google Scholar searches, reference lists, and personal contacts. Findings from the collected literature were reviewed and categorized into sand dam hydrology, health and wellbeing impacts, economic cost and benefits, and water quality topics. In most numerical simulations, sand dams supply water to the local community throughout much of the dry season and exhibit a long-term positive impact on groundwater. Accounts of water storage and loss based on field measurements, conversely, often show that most water is lost due to evapotranspiration and seepage from the sand reservoir rather than community use. Furthermore, the positive impact on local groundwater storage, while variable, is likely seasonal. Sand dams are relatively affordable to build; construction estimates range from 6000 to 8500 EUR. However, existing literature suggests that sand dams are likely not a cost-efficient means of supplying water. Nevertheless, successful sand dams can significantly increase water availability and use, whilst reducing travelling time for water collection, subsequently providing a host of secondary benefits from improved hygiene, economic opportunity, and education. Positive impacts, however, are not equally shared and depend on variables such as abstraction method, catchment, and household location. Furthermore, their water quality is variable, with high microbiological levels detected especially in scoop holes. Whilst sand dams can increase water security and resilience, they may not be an inclusive solution for all. More research is needed to assess the long-term sustainability of sand dams while accounting for the uncertainty of a changing climate.